DEVELOPMENT OF STUDENTS' INTERESTS IN THE FIELD OF HUMANITIES EDUCATION - Ulugbek Mashrabjonov (Journals Park Publishing, 2022)
In modern social conditions, it is of particular relevance  the problem of the formation of general cultural competencies and its important component - social and humanitarian competence as an integral quality of training  specialists for professional activities in the legal field.
Keywords: competence; cultural; essence